“MEMBUMIKAN MULTIKULTURALISME” - Bukhori, Imam (Humanistika : Jurnal Keislaman, 2019)
ABSTRACTThe process of multiculturalism earthing is an interesting and quite challenging phenomenon. Multiculturalism which assumes the acceptance of various diverse cultures / cultures is a sunnatullah that we cannot avoid. Therefore, a process is needed to always implement the acceptance by always trying to ground multiculturalism. The process can be done by inheriting culture / culture both through the process of socialization, enculturation, and internalization which starts from the smallest organ of society, namely individuals to large organs of society, namely educational institutions, community organizations and other government institutions. Education on the basis of multiculturalism assumes equal opportunities for each student to realize his full potential, preparing students to participate fully in an intercultural society, preparing teachers to facilitate effective learning regardless of similarities or cultural differences with him, the active participation of the school in eliminating oppression in all its forms, education must be centered on learners by listening to the aspirations and experiences of students, educators, activists, and others must take a more active role in reviewing all educational practices, including learning theory, teaching approaches, evaluation, psychology and guidance, educational material and textbooks, and others.Keywords: multiculturalism, cultural inheritance, cultural education